2019
DOI: 10.3390/en12091819
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Digestion Technology for Methane Production Using Deer Manure Under Different Experimental Conditions

Abstract: Anaerobic digestion (AD) is an important technology for the treatment of livestock and poultry manure. The optimal experimental conditions were studied, with deer manure as a fermentation material and mushroom residue as an inoculum. At the same time, methane production was increased by adding zeolite and changing the magnetic field conditions. The results showed that a 6% solid content was the best condition for producing methane. The optimal conditions for methane production were obtained by adding 35 g of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 85 publications
0
19
0
Order By: Relevance
“…B, 50°C F I G U R E 7 Cumulative biogas production at different temperatures F I G U R E 8 Cumulative biogas production of each proportion at different temperatures 47.0%-53.8%. 21 As shown in Figures 2 and 3, the biogas yield by AD of mixing deer manure and mushroom fungus was significantly lower than that of mixing deer manure, cow dung, and mushroom fungus, because the mixing of various materials can overcome the deficiency of unbalanced nutrient content in single material AD and provide a better environment for the growth of anaerobic microorganisms, thereby significantly improving biogas production. 42 The maximum potential of biogas production by AD of cow dung alone is significantly lower than that of mixing deer manure, cow dung, and mushroom fungus.…”
Section: Relationship Between Cumulativementioning
confidence: 96%
See 4 more Smart Citations
“…B, 50°C F I G U R E 7 Cumulative biogas production at different temperatures F I G U R E 8 Cumulative biogas production of each proportion at different temperatures 47.0%-53.8%. 21 As shown in Figures 2 and 3, the biogas yield by AD of mixing deer manure and mushroom fungus was significantly lower than that of mixing deer manure, cow dung, and mushroom fungus, because the mixing of various materials can overcome the deficiency of unbalanced nutrient content in single material AD and provide a better environment for the growth of anaerobic microorganisms, thereby significantly improving biogas production. 42 The maximum potential of biogas production by AD of cow dung alone is significantly lower than that of mixing deer manure, cow dung, and mushroom fungus.…”
Section: Relationship Between Cumulativementioning
confidence: 96%
“…43 The results of AD of deer manure showed that the cumulative biogas production was less than 0.02 m 3 ·kg −1 and the CH 4 content was less than 50%. 21 As shown in Figures 2 and 3, the biogas yield by AD of mixing deer manure and mushroom fungus was significantly lower than that of mixing deer manure, cow dung, and mushroom fungus, because the mixing of various materials can overcome the deficiency of unbalanced nutrient content in single material AD and provide a better environment for the growth of anaerobic microorganisms, thereby significantly improving biogas production. 44 By comparing the U2, U3, and U4 experimental groups, it can be seen that the cumulative biogas production of U3 experimental group is the highest, and the CH 4 content is 60%-70% at 50°C.…”
Section: Relationship Between Cumulative Biogas Production the Fermentioning
confidence: 96%
See 3 more Smart Citations